On HPM approximation for the perihelion preces-sion angle in general relativity - Shchigolev, Victor; Bezbatko, Dmitrii (International Journal of Advanced Astronomy, 2017)
In this paper, the homotopy perturbation method (HPM) is applied for calculating the perihelion precession angle of planetary orbits in General Relativity. The HPM is quite efficient and is practically well suited for use in many astrophysical and cosmological problems. For our purpose, we applied HPM to the approximate solutions for the orbits in order to calculate the perihelion shift. On the basis of the main idea of HPM, we construct the appropriate homotopy that leads to the problem of solving the set of linear algebraic equations. As a result, we obtain a simple formula for the angle of precession avoiding any restrictions on the smallness of physical parameters. First of all, we consider the simple examples of the Schwarzschild metric and the Reissner - NordstrÃ¶m spacetime of a charged star for which the approximate geodesics solutions are known. Furthermore, the implementation of HPM has allowed us to readily obtain the precession angle for the orbits in the gravitational field of Kiselev black hole.